Onyima custom among the Igbo of Nigeria: rethinking high fertility and prospects for change. (2015)
Nigeria is classified among high fertility countries, which despite sustained campaigns, has experienced very slow rate of fertility reduction. The Igbo ethnic group contributes substantially to the country’s prevailing fertility regime. Population pressure in Igbo sub-groups is a product of patriarchy and specific reproductive practices. This study examined onyima, which is a relatively less emphasized pronatalist custom among the Igbo, as way of understanding the inherent ideology and the feasibility of fertility reversal in relevant contexts. Data were collected through 16 in-depth interviews, 8 focus group discussions and 456 questionnaires. We discuss the implications of the findings and note that intervention should target modifications that will be sensitive to the complexity and interests of different stakeholders in order to make necessary community adaptation inclusive.